Amiodarone and amplitude spectral area of ventricular fibrillation in patients with out-of-hospital cardiac arrest. (14th October 2021) - Gentile, F R; Compagnoni, S; Baldi, E; Aramendi, E; Primi, R; Bendotti, S; Currao, A; Contri, E; Palo, A; Savastano, S
Abstract: Background: Ventricular fibrillation is the most common cause of out-of-hospital cardiac arrest (OHCA) and the use of antiarrhythmic drug therapy is usually recommended in addition to defibrillation. The role of the amplitude spectral area (AMSA) of ventricular fibrillation as a predictor of defibrillation efficacy has been established, while the existing data in favour of the use of amiodarone has been assessed with poor evidence and controversy. Purpose: The aim of our study is to evaluate whether the administration of amiodarone during resuscitation could affect AMSA values. Materials: All the OHCAs with a shockable presenting rhythm and attempted resuscitation which occurred from January 2015 to June 2019 in the province of Pavia were considered. Both the end-tidal CO2 (ETCO2) and AMSA values were calculated by retrospectively analyzing the data collected by the Corpuls 3 monitors/defibrillators (Corpuls, Kaufering, Germany) used in the territory and by considering a pre-shock interval of 2 seconds. Results: Among a total of 3413 OHCAs, resuscitation was attempted in 2195 cases (64%), 377 (17%) had a shockable presenting rhythm and in 112 cases (3.4%) it was possible to obtain the values of ETCO2 and AMSA for a total of 391 shocks. Among these, 301 shocks (77%) were delivered to patients who received amiodarone during resuscitation. The success rate of each single shock was similar in the two groups but with an unfavorable trend for amiodarone (amiodarone 43.5% vs no amiodarone 54.4%, p=0.07). AMSA was significantly lower in patients treated with amiodarone (7.9 mV·Hz, IQR 5.4–12.2 vs 10.6 mV·Hz, IQR 7.1–14.1; p<0.001). According to a multivariate analysis, the administration of amiodarone and the time to shock were independent predictors of AMSA values. Lastly, on a sample of 124 shocks, homogeneous for age, sex, ETCO2, outcome of resuscitation and randomly matched, the AMSA of patients who received amiodarone was significantly lower (7.2 mV·Hz, IQR 7.2–11.7 vs 9.7 mV·Hz, IQR 6.7–12.5; p=0.02). Conclusions: Our results indicate that amiodarone administration is associated with lower values of AMSA. Since higher AMSA values are known to be associated with a higher probability of shock rate success, this could help to better clarify the controversial role of amiodarone administration in patients with OHCA. Funding Acknowledgement: Type of funding sources: None.